On boundaries and difference: Communities of practice and power relations in creative work. Issue 3 (July 2014) - Contu, Alessia
Tensions and struggles are a usual occurrence when knowledge 'to get the job done' needs to be produced at the boundaries of different disciplines and skills. Yet, power struggles have been often overlooked, and a deeper understanding of power dynamics in, and between, communities of practice is needed. An ethnographic study of the work practices of a digital media agency is utilised as a basis for the conceptual work of addressing tensions and struggles evident in creative design work. The approach developed here reactivates the critical and relational perspectives of communities of practice theory rearticulating it with the insights of Laclau and Mouffe's site ontology. This study offers a transformative redefinition of communities of practice's existing theoretical kit. It also shows how creative abrasions are situated in the broader politics of management and organisation of creative design work.